Analysis of The Effect of Changes in Thickness and Infill Density of Thermoplastic Polyurethane and Polyethylene Terephthalate Glycol Materials as a Radiological Phantom - Yunianto, Mohtar; Cari, Cari; Sari, Arum Putri Kurnia (Graduate School of Universitas Syiah Kuala, 2024)
Phantoms are used to research image quality and the amount of attenuation as an organ simulation. If done in the human body, it would be hazardous. High radiation exposure can damage cells. Therefore, the phantom is made to resemble the properties and characteristics of a tissue so that the absorbed dose value can be analyzed according to the tissue in the organ. One use of 3D printing technology is in making phantoms. Radiology phantoms must have the same characteristics as human body tissue. This research varies the thickness and infill density of the phantom to get the suitable phantom based on material density, CT number, electron density, and effective dose. The materials used are Thermoplastic Polyurethane (TPU) and Polyethylene Terephthalate Glycol (PETG) with thickness variations of 1 cm, 2 cm, 3 cm, 4 cm, and 5 cm, and infill density variations of 20%, 40%, 60%, 80% and 100 %. Based on the test parameters carried out, it was found that changes in thickness did not affect the material density, EDG, EDV, and Z eff of the sample. However, changes in thickness are proportional to the CT number and electron density values. Meanwhile, changes in infill density are proportional to changes in material density values, CT number, electron density, and EDV. However, changes in infill density do not affect the EDG and Z eff values. The values obtained for each parameter are compared with the reference organ. Samples made from TPU and PETG are suitable for lung, muscle, soft tissue, and spongy bone.